KOMPENSASI CHIEF EXECUTIVE OFFICER (CEO) DAN KINERJA PERUSAHAAN - Harjum Muharam (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACTThere are two main topics when we took about Chief Executive Officer compensation, the first one is relationship between CEO compensation and shareholder interest that was knew as agency problem. The second one is about amount and mix of CEO compensation and it impact on corporate performance. Entry benefits and exit benefits are the one-off pecuniary that gift to CEO once during his/him duties. Ongoing benefits consist of fixed payment and at risk payment—short-tem incentives (STIs) and long-term incentives (LTIs). Every kind of that compensation has special impact on CEO behaviour that shareholder want. Beside that compensations there is non-financial pecuniary that also has the same impact. Many persons argue that COEs are overpaid and that their compensation amounts are excessive and inequitable. The reason for this is because CEO has more complexity and responsibility job than the others in the company and has bigger contribution for company performance. Depend on latest research, there is positive and significantly relationship between CEO compensation and company performance.Keywords : Compensation; CEO (Chief Executive Officer); Corporate Performance